Inviting foreign direct investment for sports development projects in relation to economic development and development challenges - Mostafa Mohamed, Samir Abdel Latif; Khalil Sayyd, Sameer Mohammed; Mohamed Ghreeb, Mohamed Soliman (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The present study aimed to investigate attracting foreign direct investment for sports development projects in relation to economic developments and challenges. The researchers utilized a descriptive approach, using a questionnaire, due to its appropriateness for the nature of the research. A total of 300 workers from the General Office of the Ministry of Youth and Sports participated in this study. They were selected using a stratified purposeful sampling method from the following categories: undersecretaries, general directors, department directors, department heads, and administrators. The findings of this study showed support for foreign trade exchanges through investment in export industries, especially in contexts where the host country has an advantage over the country of origin and where banking facilities are available in commercial banks. Additionally, it was demonstrated that lower risk and higher returns lead to an influx of investments. Consequently, this increases capital formation, particularly by reducing the state’s dependence on external debt and decreasing the volume of foreign aid.